2010
DOI: 10.1007/s10549-010-0780-8
|View full text |Cite
|
Sign up to set email alerts
|

Worse prognosis of metaplastic breast cancer patients than other patients with triple-negative breast cancer

Abstract: The present study was designed to assess the clinical characteristics and outcomes of metaplastic breast cancer (MBC) compared to general invasive ductal carcinoma (IDC) and the triple-negative subtype (TN-IDC). The study population included 35 MBC and 2,839 IDC patients, including 473 TN-IDC diagnoses, from the National Cancer Center, Korea between 2001 and 2008. The clinicopathological characteristics and clinical outcomes were retrospectively reviewed. Mean age of patients was 47.4 years for the MBC group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
193
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(221 citation statements)
references
References 28 publications
24
193
2
2
Order By: Relevance
“…Estrogen receptor positivity was ranging from 0 to 19.2%, Pr positivity was 0 to 35.7%, HEr2 expression was 0 to 15.7% and Tn was 80.4 to 100% (14, 15, 21-27). Jung et al also indicated that frequency of a Tn status was higher in MCs than invasive ductal carcinomas (28). Similarly, we found only 1 case to be positive for Er, only 2 cases to be Pr-positive and HEr2 over expression to be present in only one SCC.…”
Section: Discussionsupporting
confidence: 81%
“…Estrogen receptor positivity was ranging from 0 to 19.2%, Pr positivity was 0 to 35.7%, HEr2 expression was 0 to 15.7% and Tn was 80.4 to 100% (14, 15, 21-27). Jung et al also indicated that frequency of a Tn status was higher in MCs than invasive ductal carcinomas (28). Similarly, we found only 1 case to be positive for Er, only 2 cases to be Pr-positive and HEr2 over expression to be present in only one SCC.…”
Section: Discussionsupporting
confidence: 81%
“…Reduced sensitivity of breast cancers to anticancer drugs has frequently been associated with an epithelial-to-mesenchymal transition (EMT) (4)(5)(6)(7). Metaplastic breast carcinomas (MBCs) are a subset of triple-negative breast cancers (TNBCs) characterized by a claudin-low and EMT-like phenotype (8) and a poor prognosis compared with other TNBCs (9). More than 60% of MBCs have BRCA1 promoter methylation, raising the question whether these tumors can be effectively targeted by using PARP inhibitors (10).…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Metaplastic carcinoma of the breast typically presents at a more-advanced stage than either invasive ductal or lobular adenocarcinoma cases and, in general, has a worse prognosis. 6,7 On routine biomarker testing for estrogen receptor (ER) and/or progesterone receptor (PR) status, most MPBCs are negative. 8 Similarly, virtually all MPBC cases are negative for HER2 overexpression and amplification by either immunohistochemistry (IHC) and/or fluorescence in situ hybridization.…”
mentioning
confidence: 99%